Larval morphology and advertisement call of Phyllodytes acuminatus Bokermann, 1966 (Anura: Hylidae) from Northeastern Brazil - Campos, Thamires F.; de Lima, Marcelo G.; Nascimento, Filipe Augusto C. Do; Dos Santos, Ednilza M. (Zootaxa, 2014)
This paper describes the tadpole and advertisement call of Phyllodytes acuminatus, based on specimens from the Parque Nacional do Catimbau, in the municipality of Buíque, State of Pernambuco, Northeastern Brazil. The overall morphology of P. acuminatus tadpole is similar to that of most species of the genus. The presence of a double row of marginal papillae surrounding all the oral apparatus (except on most of the upper labium which has a dorsal gap) was a characteristic that differentiate P. acuminatus from the other species of the genus. Furthermore, the call structure of the species (unpulsed notes with harmonic structure) fits it in the group composed of P. kautskyi and P. melanomystax.